2010
DOI: 10.1007/s11670-010-0303-5
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-18 suppresses angiogenesis and lymphangiogenesis in implanted Lewis lung cancer

Abstract: Objective:To investigate the effects of interleukin-18 (IL-18) on implanted Lewis lung cancer in suppressing angiogenesis and lymphangiogenesis.Methods: One week after hypodermic inoculation of Lewis cells, sixteen tumor-bearing syngeneic mice were randomly divided into two groups. The mice in the treatment group (group A) were intraperitoneally injected with the IL-18 and in the control group (group B) were intraperitoneally injected with normal saline for 7 days. The mice were killed on day 19. The morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Although ATG16L1 plays an essential role in autophagy, and is part of a larger protein complex ATG16L1-ATG5-ATG12 that is necessary for autophagy, ATG16L1 is also involved in the production of inflammatory cytokines IL-1β and IL-18 and exerts anti-inflammatory functions during intestinal inflammation (Cadwell et al, 2008; Diamanti et al, 2017; Saitoh et al, 2008; Sorbara et al, 2013). IL-1β promotes angiogenesis by activating VEGF production during tumor progression (Carmi et al, 2013; Voronov et al, 2003), while IL-18 suppresses angiogenesis in cancer (Cao et al, 1999; Xing et al, 2016; Yang et al, 2010). How ATG16L1 regulates angiogenesis through inflammatory cytokines and whether this regulation operates downstream of PKA activity in vivo requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Although ATG16L1 plays an essential role in autophagy, and is part of a larger protein complex ATG16L1-ATG5-ATG12 that is necessary for autophagy, ATG16L1 is also involved in the production of inflammatory cytokines IL-1β and IL-18 and exerts anti-inflammatory functions during intestinal inflammation (Cadwell et al, 2008; Diamanti et al, 2017; Saitoh et al, 2008; Sorbara et al, 2013). IL-1β promotes angiogenesis by activating VEGF production during tumor progression (Carmi et al, 2013; Voronov et al, 2003), while IL-18 suppresses angiogenesis in cancer (Cao et al, 1999; Xing et al, 2016; Yang et al, 2010). How ATG16L1 regulates angiogenesis through inflammatory cytokines and whether this regulation operates downstream of PKA activity in vivo requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In line with data emerging from studies on the eye, IL-18 has also been shown to inhibit neovascularisation in murine fibrosarcoma and suppress growth, an anti-angiogenic function that suggests it may have a role in some contexts as a tumor suppressor (63). IL-18 also suppressed tumor growth and metastasis in implanted Lewis lung cancer, an effect it achieved by downregulating VEGF, thereby suppressing angiogenesis (78). This data implies that IL-18 down regulation of VEGF is not unique to the eye but is observed in non-ocular tissue as well.…”
Section: Il-1—an Extensive Mediator Of Angiogenesismentioning
confidence: 99%
“…Although ATG16L1 plays an essential role in autophagy, and is part of a larger protein complex ATG16L1-ATG5-ATG12 that is necessary for autophagy, ATG16L1 is also involved in the production of inflammatory cytokines IL-1β and IL-18 and exerts antiinflammatory functions during intestinal inflammation (Cadwell et al, 2008;Diamanti et al, 2017;Saitoh et al, 2008;Sorbara et al, 2013). IL-1β promotes angiogenesis by activating VEGF production during tumor progression (Carmi et al, 2013;Voronov et al, 2003), while IL-18 suppresses angiogenesis in cancer (Cao, Farnebo, Kurimoto, & Cao, 1999;Xing et al, 2016;Yang, Chen, Lu, Li, & Lin, 2010). How ATG16L1 regulates angiogenesis through inflammatory cytokines and whether this regulation operates downstream of PKA activity in vivo requires further investigation.…”
Section: Discussionmentioning
confidence: 99%